Chasing the perfida Albione: Anglo-Italian productivity gap in the late thirties - Tancredi Salamone (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2025)
In this paper, I introduce new estimates of Anglo-Italian labour productivity levels in manufacturing during the late 1930s. The relatively high level of detail of the industrial censuses of the two countries, allows to retrieve also input data, enabling the use of the more sophisticated double deflation method. This approach treats outputs and inputs separately, thereby considering the input-output structure of the compared countries. These estimates, in turn, allow me to extend the analysis to other countries for which similar comparisons with the UK have already been made. I also provide preliminary estimates of labor productivity on a per-hour basis. The results point to a significant productivity gap at the aggregate level, with intersectoral heterogeneity being the prevailing pattern. Notably, Italian performance stands out favorably in textiles and, to a lesser extent, in iron and steel production and the chemical sector. Ultimately, these estimates, while affirming the substantial gap highlighted in other studies, actually propose an upward revision of the Italian productivity level.
Keywords: N14; N64; O14; O47; 330; Productivity; Italy; UK; Manufacturing; Fascism